Pengaruh laju Aliran Air Terhadap Temperatur Sistem Mesin Pengkondisian Udara Hibrida Menggunakan Kondensor Dummy Tipe Helical Coil (Diameter Pipa 1/4") Sebagai Water Heater Dengan Pembebanan 2000 Watt - Mainil, Rahmat Iman; Anam, Khoirul; Aziz, Azridjal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Energy saving is one way to reduce energy usage without decreasing the results. This way can be obtained byusing the hybrid air conditioning. Other than energy saving, the hybrid air conditioning also can reduce theeffects of global warming by condenser waste heat recovery. This research aims to investigate the effect ofvariations flow rate in water heater tank to the system temperatures of hybrid air conditioning using helical coiltype of dummy condenser with 1/4Ë diameter of copper pipe. Experimental method is used in this research. Thetest was conducted with several water flow rate variations (1/3, 2/3, and 3/3 valve openings) and using coolingload of 2000 Watt as residential cooling load simulation. The result showed that the water temperature in waterheater tank was changed in every water flow rate variations. The highest water temperature was obtained at39.77ËšC for 0 valve opening (full-closed valve), but, the lowest water temperature was obtained at 32.57ËšC in3/3 valve opening (full-open valve).Keywords: water heater, helical coil, dummy condenser.